Incidencia de porcentajes de goma guar y zumo de maracuyá (Passiflora edulis) en la calidad fisicoquímica y organoléptica del néctar - Buste Mendoza, Victor Alfonso (2017)
The objective of the research was to evaluate the incidence of percentages of rubber guar and passion fruit juice (Passiflora edulis) in the physico-chemical and organoleptic quality of the nectar. To establish the ideal formulation, we used a design completely at random (DCA) in A a bivariate array * B (3 * 2) with three replicas per treatment, as factors it used factor percentages of rubber with 3 levels (0.2% 0.3%; 0 4%), B 2 levels were used (15%, 20%), were evaluated parameters viscosity, density, pH, sensory, protein, lipids, carbohydrates and microbiological. It was the statistical non-parametric Kruskal Wallis at 5% of significance. The results showed that A factor was statistically significant for the variables pH and viscosity but not in density, likewise for the treatments. Factor B was not statistically significant. In conclusion the best treatment was the T4 (0.3% of rubber guar and 20% juice) with a production cost of $ 0.91/L, pH 3.4 values; 42 Cps viscosity and density 1.07 g/c3, sensually was greater acceptance by the panelists, microbiologically met provisions of Norma INEN 2337 - 2008.